2006
DOI: 10.1039/b609507k
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene-sensitized electron transport across vesicle bilayers: dependence of transport efficiency on pyrene substituents

Abstract: Endoergic electron transport across vesicle bilayers from ascorbate (Asc-) in the inner waterpool to methylviologen (MV2+) in the outer aqueous solution was driven by the irradiation of pyrene derivatives embedded in the vesicle bilayers. The initial rate of MV2+ reduction is dependent on the substituent group of the pyrenyl ring; a hydrophilic functional group linked with the pyrenyl ring by a short methylene chain acts as a sensitizer for the electron transport. Mechanistic studies using (1-pyrenyl)alkanoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The precursor SiPcCl 2 was synthesized according to the procedures of Lo et al and Lim et al ( Scheme 1 a) . 1‐Pyrenecaxboxlic acid, 1‐pyreneacetic acid, and 1‐pyrenebutyric acid were purchased from Sigma Aldrich and used without further purification, while 1‐pyrenepropionic acid 6 was synthesized according to the reported procedure (Scheme b) . Silicon phthalocyanines SiPc‐Py‐1, SiPc‐Py‐2, SiPc‐Py‐3, and SiPc‐Py‐4 were synthesized as described in Scheme c.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor SiPcCl 2 was synthesized according to the procedures of Lo et al and Lim et al ( Scheme 1 a) . 1‐Pyrenecaxboxlic acid, 1‐pyreneacetic acid, and 1‐pyrenebutyric acid were purchased from Sigma Aldrich and used without further purification, while 1‐pyrenepropionic acid 6 was synthesized according to the reported procedure (Scheme b) . Silicon phthalocyanines SiPc‐Py‐1, SiPc‐Py‐2, SiPc‐Py‐3, and SiPc‐Py‐4 were synthesized as described in Scheme c.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the same reaction conditions applied to phthalate 5 only resulted in alkyne decomposition and a mixture of unidentified by‐products. Catalytic reduction of the triple bond of 9 has been described with PtO 2 (15 mol %) in THF, but we found that much cheaper Pd/C in methanol worked just as well, with a lower catalyst loading (5 mol %) and shorter reaction times (20 min); thus resulting in an overall dramatic decrease in the reaction cost.…”
Section: Resultsmentioning
confidence: 76%
“…Although classical Sonogashira conditions are described as being effective for the reaction of propargyl alcohol (8)w ith 2, [16] in our hands only copper-free conditions, with [Pd(PPh 3 ) 4 ] as ac atalyst in nBuNH 2 at reflux, gave the desired product 9 in excellent yield (94 %; Scheme 3). [17] It is worth noting that the same reaction conditions appliedt op hthalate 5 only resulted in alkyne decomposition and am ixture of unidentified by-products.C atalytic reduction of the triple bond of 9 has been described with PtO 2 (15 mol %) in THF, [18] butw ef ound that much cheaper Pd/C in methanol workedj ust as well, with a lower catalyst loading (5 mol %) and shorterr eaction times (20 min);t hus resulting in an overall dramatic decrease in the reactioncost.…”
Section: Resultsmentioning
confidence: 99%
“…Feringa's research into nano-cars may provide one example of this, although his team's experiment was conducted using an intermittent electric current rather than continuous light waves [15]. Photo-induced ion or electron transportation across membranes [16,17] provides further instances of this phenomenon [5]. However, to attain more significant autonomous work at the multi-molecular scale, the concept of dissipative self-organization is required.…”
Section: Research Aiming Mechanical Work With Energy Conversionmentioning
confidence: 99%